PHYSICAL TRAINING OF BEGINNER TENNIS PLAYERS AT THE AGE OF 8-10 - MOISESCU P.C; BUCĂTARU R.M (Editura Universitatii Transilvania din Brasov, 2020)
Every day, tennis becomes an increasingly physical sport due to the equipment and the technology used in their construction. The material from which tennis rackets are made, the strings and balls currently used, gives the game a much higher speed. If at first, in tennis, the main skill was coordination I tend to think that nowadays the percentage of other skills, somehow balances the balance. In this paper I want to observe the difference between classical physics training and the modern method of "tennis 10" physics training in athletes 8-10 years old